Possible Impacts of Human Enhancement Technologies on the Older Workforce - Kutluğ Kağan Karahan; Elif Yüksel Oktay (Sosyal Siyaset Konferansları Dergisi)
The importance given to Human Enhancement Technologies (HET) in the literature is increasing daily. Both the fact that the technologies available today will become widespread in the future and the technologies that we are close to reaching because of rapidly continuing research, HET will become a part of both our daily lives and work life in the future. The elderly population continues to increase both in number and proportion of the total population. It is estimated that this change will be reflected in the labour market shortly and that the older workforce will account for almost half of the total labour force. There are several issues that reduce the employability of older people. In general, older people are associated with illness, disability, memory loss and cognitive decline, physical decline, loneliness and depression. They are also perceived to be more costly in enforcing health and safety standards. HET can help to overcome some of the problems faced by the older workforce. In this study, the concept of HET will be discussed, and the effects of HET on the older workforce in the labour market will be evaluated.